THE RELEVANCE OF THE CENTRALIZED AND DECENTRALIZED ZAKAT MANAGEMENT IN POVERTY ALLEVATION IN INDONESIA (VIEW OF UMAR BIN ABDUL AZIZ) - Umami, L. D.; Syamsuri (Farabi Journal of Social Sciences, 2023)
The problem of poverty in Indonesia is still unresolved until now. Zakat is one of the instruments to alleviate poverty according to Islam. Even the main purpose of zakat is to alleviate poverty. Indeed, zakat has been implemented in Indonesia, however, the centralization management system that has been implemented still cannot alleviate poverty. This study employed qualitative method with content analysis and research data sources from published sources, both classical and contemporary literature or presents data from interviews with zakat experts and practitioners, includes elements BAZNAS (National Zakat Agency) and LAZ. The other data were books, jounals, and others.This study aims to determine the policy of Umar bin Abdul Aziz in his day as well as actualize charity in seeking relevance to modern policy of zakat in Indonesia, both in the form of fatwas of the scholars or regulatory policy in the form of legislation. The result of this study is to switch the policy to a decentralized system, as it has already proven its success when it was implemented by Umar bin Abdul Aziz. Muslims at that time were prosperous, until no more mustahiq zakat was found. Keywords: poverty, centralization, decentralization, Umar bin Abdul Aziz.